(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article investigates similarities and distinctions in the gender-specific use of diminutives in English and Uzbek literary discourse. The study is based on Roald Dahl’s Charlie and the Chocolate Factory and Khudoyberdi Tokhtaboyev’s Sariq devni minib. Special attention is paid to how diminutives express affection, emotional closeness, irony, and gender-related attitudes. The analysis demonstrates that both English and Uzbek literary traditions actively use diminutives to portray children and female characters, although Uzbek discourse employs richer lexical and suffixal forms. The article also highlights sociolinguistic differences in the representation of masculinity and femininity.